2021
DOI: 10.1002/eat.23554
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cost‐effectiveness of two ways of delivering guided self‐help for people with an eating disorder: A multi‐arm randomized controlled trial

Abstract: Objective Increasing the availability and accessibility of evidence‐based treatments for eating disorders is an important goal. This study investigated the effectiveness and cost‐effectiveness of guided self‐help via face‐to‐face meetings (fGSH) and a more scalable method, providing support via email (eGSH). Method A pragmatic, randomized controlled trial was conducted at three sites. Adults with binge‐eating disorders were randomized to fGSH, eGSH, or a waiting list condition, each lasting 12 weeks. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…Based on the effectiveness of online interventions for BED ( Beintner et al, 2014 ; Haderlein, 2022 ), we expect that the program will lead to a greater reduction in the frequency of binge eating episodes over the twelve weeks of treatment compared to a waitlist control condition. Moreover, we assume that there will be a higher decline in global eating disorder symptoms and functional impairments as well as a higher increase in well-being and work capacity in the intervention group compared to the waitlist control group ( Ágh et al, 2015 , Jenkins et al, 2021 , Safi et al, 2022 ). Finally, we expect that the web-based intervention for BED will be associated with a significantly higher reduction in comorbid psychopathology, increased self-esteem, and an improved ability to regulate negative emotions after treatment ( Dingemans et al, 2017 , Linardon et al, 2019 , Prefit et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the effectiveness of online interventions for BED ( Beintner et al, 2014 ; Haderlein, 2022 ), we expect that the program will lead to a greater reduction in the frequency of binge eating episodes over the twelve weeks of treatment compared to a waitlist control condition. Moreover, we assume that there will be a higher decline in global eating disorder symptoms and functional impairments as well as a higher increase in well-being and work capacity in the intervention group compared to the waitlist control group ( Ágh et al, 2015 , Jenkins et al, 2021 , Safi et al, 2022 ). Finally, we expect that the web-based intervention for BED will be associated with a significantly higher reduction in comorbid psychopathology, increased self-esteem, and an improved ability to regulate negative emotions after treatment ( Dingemans et al, 2017 , Linardon et al, 2019 , Prefit et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The WHO-5 assesses general well-being based on five items, rated on a 6-point scale, and has high internal consistency (Cronbach's α = .92; Brähler et al, 2007 ). Changes in w ork capacity : To address the increasing significance of health economic evaluations ( Jenkins et al, 2021 ; Safi et al, 2022 ), changes in work capacity and productivity will be measured based on the iMTA Productivity Cost Questionnaire (iPCQ; Bouwmans et al, 2015 ). The iPCQ examines absences from work and productivity losses due to sickness-related restrictions in work efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals who, at assessment with the service, met criteria for a diagnosis of BN, BED, or OSFED participated in a randomised controlled trial of guided self-help with few exclusion criteria (see [ 25 ]), and data from these individuals were included in the current study (see Table 1 ). Conduct of the trial was approved by an ethics review board (details are reported elsewhere [ 26 ]) and the study was performed in accordance with the ethical standards as laid down in the 1964 Declaration of Helsinki and its later amendments.…”
Section: Methodsmentioning
confidence: 99%
“…As an example from outside of the social sciences, researchers might design different iterations of polymer networks of the same drug to determine the most effective drug-delivery system (Efentakis & Politis, 2006). In the social sciences, this can be, for example, manipulating the delivery techniques and media style (e.g., providing guided self-help via face-to-face meetings vs. via email to address eating disorders; Jenkins et al, 2021) of the same source materials or examining the optimal dose of an intervention (e.g., one vs. three sessions of exposure therapy to prevent the development of posttraumatic stress disorder; Maples-Keller et al, 2020).…”
Section: Intervention Tournamentsmentioning
confidence: 99%
“…This highlights the (in-house-developed) intervention tournament as a tool to test different iterations of a similar intervention to zero in on the most effective one. In other words, in most cases, the core is similar, whether it is a drug (Efentakis & Politis, 2006) or the psychological content (Bruneau et al, 2022; Jenkins et al, 2021; Maples-Keller et al, 2020; Milkman et al, 2011; Rosler et al, 2021) that is administered, but the delivery is different in each of these interventions.…”
Section: Intervention Tournamentsmentioning
confidence: 99%